2021
DOI: 10.1186/s12877-020-01976-z
|View full text |Cite|
|
Sign up to set email alerts
|

Intergenerational caring: a systematic literature review on young and young adult caregivers of older people

Abstract: Background The theme of young family caregivers of older relatives is still partially uncovered, although the phenomenon is increasing worldwide. This Systematic Literature Review discusses methodological and content issues of ten articles covering this topic, in order to contribute to increase the knowledge and provide suggestions for designing effective support services for adolescent young caregivers. To this purpose, the findings of this review are framed within the caregiving stress apprai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 61 publications
2
31
0
Order By: Relevance
“…17 Overall however, there has been little work done to quantitatively examine the mental health impact of caring on young people and this lack of quantitative work among young carers using large samples has been recognised in a recent review. 18 Furthermore, most studies of mental health among young carers have used single or two item measures of mental health, and only a minority have used validated measures. In addition to this, there is a lack of quantitative research of young informal carers in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…17 Overall however, there has been little work done to quantitatively examine the mental health impact of caring on young people and this lack of quantitative work among young carers using large samples has been recognised in a recent review. 18 Furthermore, most studies of mental health among young carers have used single or two item measures of mental health, and only a minority have used validated measures. In addition to this, there is a lack of quantitative research of young informal carers in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…A better understanding of their needs is a priority, as defined by the World Health Organization [8]. Recent reviews showed that unmet needs of PIC have to be taken into account in a proactive approach of care planning from health care professionals, and that PIC are often not integrated enough in the health care system [9][10][11]. In 2011, the Belgian Health Care Knowledge Centre analyzed thirty forms of non-pharmaceutical therapy for people with dementia.…”
Section: Introductionmentioning
confidence: 99%
“…The literature confirms that in Italy the family remains the strongest provider of care, especially for older people with limited physical functionalities and disabilities, and almost always represents the first choice for obtaining support, especially when compared to the alternatives of scarce public home care and residential services [ 26 ]. Very strong intergenerational ties, therefore, persist at the basis of informal caregiving towards older people, with social and cultural norms that establish family responsibilities [ 92 , 93 , 94 ].…”
Section: Discussionmentioning
confidence: 99%